2017
DOI: 10.1016/j.electacta.2017.08.099
|View full text |Cite
|
Sign up to set email alerts
|

Loading effect of carbon-supported platinum nanocubes on oxygen electroreduction

Abstract: Loading effect of carbonsupported platinum nanocubes on oxygen electroreduction, Electrochimica Actahttp://dx. Graphical abstract Research highlights Cubic Pt nanoparticles are synthesised in the presence of oleylamine and oleic acid  Vulcan carbon is used as a support for cubic Pt nanoparticles with various loading  Pt/C catalysts revealed a high ORR activity in both acid and alkaline solutions  Pt/C catalysts showed similar specific and mass activity independently of Pt loading  Important methodological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 80 publications
(126 reference statements)
3
22
0
Order By: Relevance
“…The differences in dissolution observed here may also correlate to the stability towards dissolution of preferentially shaped Pt or Pt alloy nanoparticles, which show great promise in terms of activity . It could be hypothesized that octahedral shaped nanoparticles exposing Pt(111) facets dissolve less than cubic shapes exposing Pt(100).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in dissolution observed here may also correlate to the stability towards dissolution of preferentially shaped Pt or Pt alloy nanoparticles, which show great promise in terms of activity . It could be hypothesized that octahedral shaped nanoparticles exposing Pt(111) facets dissolve less than cubic shapes exposing Pt(100).…”
Section: Discussionmentioning
confidence: 99%
“…In the quest to improve electrocatalyst activity towards the oxygen reduction reaction (ORR) and reduce the required quantities of platinum in the CL, one promising strategy is the use of platinum and platinum alloy nanoparticles with preferential shapes exposing the low index face-centered cubic crystal facets. [19][20][21][22][23][24][25][26][27] Although activity trends have been identified among the varied shapes and exposed facets, reaching firm conclusions has required the development of techniques to produced very clean surfaces. These difficulties highlight the need for well-defined systems in a bottom up approach to understanding electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[60] In addition, the enhanced ORR activity may be ascribed to the superior electrical conductivities of Pt/rGOÀN composites. The highest SA value of 0.22 and 0.38 mA cm À2 in acidic and alkaline media, respectively, was obtained for Pt/rGOÀN catalyst.…”
Section: Electrochemical Reduction Of Oxygenmentioning
confidence: 99%
“…The O binding energy is related to the proton‐electron transfer mechanism, which determines the electrocatalytic activity of the ORR. Recently, a lot of researchers have been dedicated to design Pt‐based catalysts with different morphologies including nanocubes, nanowires, core‐shell structures, hollow structures, and alloys ,,. However, the high metal price and the low earth reserve of the Pt limit their industrial applications, as shown in Figure b .…”
Section: The Oxygen Reduction Reaction and Its Electrochemical Evaluamentioning
confidence: 99%
“…Recently, a lot of researchers have been dedicated to design Pt-based catalysts with different morphologies including nanocubes, nanowires, core-shell structures, hollow structures, and alloys. [8,46,[50][51][52][53] However, the high metal price and the low earth reserve of the Pt limit their industrial applications, as shown in Figure 2b. [46] The development of transition metal (Fe, Mn, Ni, and Co etc.)…”
Section: The Oxygen Reduction Reaction and Its Electrochemical Evaluamentioning
confidence: 99%